The Tail of a Yeast Class V Myosin, Myo2p, Functions as a Localization Domain - Reck-Peterson, Samara L. (The American Society for Cell Biology, 1999)
Myo2p is a yeast class V myosin that functions in membrane trafficking. To investigate the function of the carboxyl-terminal-tail domain of Myo2p, we have overexpressed this domain behind the regulatable GAL1 promoter (MYO2DN). Overexpression of the tail domain of Myo2p results in a dominant–negative phenotype that is phenotypically similar to a temperature-sensitive allele of myo2, myo2–66. The tail domain of Myo2p is sufficient for localization at low- expression levels and causes mislocalization of the endogenous Myo2p from sites of polarized cell growth. Subcellular fractionation of polarized, mechanically lysed yeast cells reveals that Myo2p is present predominantly in a 100,000 × g pellet. The Myo2p in this pellet is not solubilized by Mg(++)-ATP or Triton X-100, but is solubilized by high salt. Tail overexpression does not disrupt this fractionation pattern, nor do mutations in sec4, sec3, sec9, cdc42, or myo2. These results show that overexpression of the tail domain of Myo2p does not compete with the endogenous Myo2p for assembly into a pelletable structure, but does compete with the endogenous Myo2p for a factor that is necessary for localization to the bud tip.